(untitled) (Entrepreneurship Journal for Finance and Business, 2022)
E-learning is one of the important means that come as a result of the dangerous epidemic of Corona pandemic, which was applied to all Iraqi, Arab and international universities to avoid the spread of this dangerous epidemic that has assaulted humanity. Hence, it’s important to study the reality of applying E-learning, also study on situation of students and the use of statistical and studies Statistical to study this reality which will become realistic in use in the coming years Among the statistics theories cluster analysis is used which is one of the important topics. A questionnaire from was distributed to student of the Ninavah Technical Institute (at the Northern Technical University). The Data included two axes, first one (exam performance) and the second (electronic exam). the sample number was 130 male and female students, and after debriefing the data, it was 11 damages questionnaires, The results were extracted and it was shown that the students’ ability to use the reality of E-learning increased and the skills and abilities to use modern education means and the internet increased.